Foundations of metacognition - Beran, Michael J. (Oxford : Oxford University Press, 2013)
Metacognition refers to the awareness an individual has of their own mental processes. In the past 30 years metacognition research has become a growing field of interdisciplinary research within the cognitive sciences. This book brings together cognitive scientists to consider some of the questions regarding this phenomenon.
Description based on online resource; title from PDF title page (viewed on Oct. 30, 2012).
Keywords: Metacognition